Private Investment and Economic Growth in Developing Countries. (IMF Working Papers; Working Paper ;, 1989)
Despite the growing support for market-oriented strategies, and for a greater role of private investment, empirical growth models for developing countries typically make no distinction between the private and public components of investment. This paper sheds some light on this important issue by formulating a simple growth model that separates the effects of public sector and private sector investment. This model is estimated for a cross - section sample of 24 developing countries, and the results support the notion that private investment has a larger direct effect on growth than does public investment.